Effects of Root Restriction and Water Stress on Growth Performance, and Physiological and Biochemical Responses of Mango (Mangifera Indica Cv. Chokanan) - Sakimin, Siti Zaharah (2006)
The effects of restricted root volume (10, 30 and 50-litre of soil) on growth,stomatal conductance and photosynthesis rate of mango (Mangifera indica) cv.Chokanan trees were investigated under a rain shelter condition.Root restriction (10-litre of soil) significantly (P